Quantifying geodiversity–vegetation relationships in the Arctic using remote sensing - Baines, Oliver (2023)
Context The Earth is changing drastically as a result of human-induced climate change. Understanding contemporary distributions of species, and what drives them, is therefore essential, in order to understand how these may change in the future. Geodiversity – the diversity of the non-climatic abiotic environment – has been shown to be correlated with biodiversity across a range of terrestrial environments. Conservation initiatives underpinned by geodiversity have emerged, suggesting that protecting geofeatures such as landforms, rock types or water bodies could act as a coarse-filter strategy for protecting biodiversity. However, key questions underpinning geodiversity–biodiversity relationships remain unanswered. The Arctic is warming nearly four-times faster than the global average, with plant communities changing rapidly as a result. Incorporating geodiversity into Arctic vegetation research could provide important insights into how and why changes are occurring, the implications of these changes, as well as providing answers to outstanding questions surrounding geodiversity–biodiversity relationships. Using data gathered across a variety of scales, this thesis examines the importance of geodiversity for explaining pan-Arctic changes in vegetation through time, as well as exploring geodiversity–vegetation relationships across very fine scales. In doing so, I explore novel methods for measuring both geodiversity and biodiversity using remote sensing, including the treatment of uncertainty. I hope to provide both evidence and tools to further demonstrate the need to consider environmental changes holistically and improve our understanding of the coupling between plants and their abiotic surroundings.